2016
DOI: 10.1071/wf15047
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of shoot flammability for 60 tree and shrub species supports rankings based on expert opinion

Abstract: Abstract. Fire is an important ecological disturbance in vegetated ecosystems across the globe, and also has considerable impacts on human infrastructure. Vegetation flammability is a key bottom-up control on fire regimes and on the nature of individual fires. Although New Zealand (NZ) historically had low fire frequencies, anthropogenic fires have considerably impacted indigenous vegetation as humans used fire extensively to clear forests. Few studies of vegetation flammability have been undertaken in NZ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 48 publications
2
107
1
6
Order By: Relevance
“…In particular, coniferous trees were the least flammable of all groups analysed. This contradicts recent work which found that the conifer rimu (Dacrydium cupressinum) was among the most flammable of 60 species trialled (Wyse et al 2016).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In particular, coniferous trees were the least flammable of all groups analysed. This contradicts recent work which found that the conifer rimu (Dacrydium cupressinum) was among the most flammable of 60 species trialled (Wyse et al 2016).…”
Section: Discussioncontrasting
confidence: 69%
“…McGlone and Basher 1995). The assumption has been that the high volatile oil content of their leaves (Cambie 1996) renders conifers particularly flammable (Fogarty 2001), but there is precious little data on the comparative foliar flammability of New Zealand's indigenous plant species from controlled combustion trials (although data on shoot-level flammability native New Zealand species have recently been published, Wyse et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…() and modified by Wyse et al. () (Figure ; Table ), with adjustments for larger plants (the vertical cylinder described above). All samples were stored air‐dry at room temperature for 24 hr before burning (Wyse et al., ) to ensure that the moisture content of the samples matched the ignition source (Wyse, Perry, & Curran, ).…”
Section: Methodsmentioning
confidence: 99%
“…Leptospermum scoparium is highly flammable (Wyse et al ., ). Our experimental assessment shows that, although flammability varies between and within populations, there is little relationship between serotiny and flammability.…”
Section: Discussionmentioning
confidence: 97%
“…() and closely following the protocol of Wyse et al . () (see Appendix S2). We measured four flammability characteristics: time to ignition (ignitability), the duration of burn (sustainability), maximum burn temperature (°C) (combustibility) and percentage of sample burnt (consumability).…”
Section: Methodsmentioning
confidence: 99%